Pentingnya Administrasi Kurikulum dalam Peningkatan Kualitas Pendidikan - Desmita, Bunga; Wenggi, Safingi; Urnia Putri, Wenti (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Curriculum administration is a key component in education, serving as a guide for planning, implementing, and evaluating the learning process. This study employs a literature review method to explore various aspects of curriculum administration, including the role of teachers, technology integration, and its impact on educational quality. The findings indicate that effective curriculum administration can enhance learning efficiency, material relevance, and the achievement of educational goals. The application of AI technology offers innovative opportunities to tailor learning to the individual needs of students. This study recommends enhancing teacher competencies through training and integrating technology to support better curriculum management.